Persebaran Emisi Karbon Dioksida (CO2) dari Aktivitas Permukiman di Kecamatan Menganti Kabupaten Gresik. - Yolanda Romadhanti; Dyah Ratri Nurmaningsih; Sulistiya Nengse; Amrullah Amrullah (Dampak, 2021)
The high level of population density in Menganti District is a potential contributor to CO2 carbon dioxide emissions. The resulting carbon emissions are from the transportation, energy, agriculture, livestock and solid waste. The formulation of the problem of this research is how much the value of carbon emissions generated from settlement activities in Menganti District and how to map the carbon footprints generated from settlement activities in Menganti District. The purpose of this study was to determine the value of carbon emissions and to map the value of carbon emissions. Based on the data obtained, the emission value of the Animal Husbandry Sector is 461.78 tons CO2-eq / year, the Waste Sector is 1537.01 tons CO2 / year, the Agriculture Sector is 2523.68 tons CO2-eq / year, the Transportation Sector is 2607, 86 tons CO2-eq / year and the Energy Sector 11203.96 tons CO2-eq / year. The results of the mapping of the highest carbon emission value for residential activities in Menganti District are Kelurahan Menganti with a range of 12275.03-16904.7 tonnes of CO2-eq /   year, the largest contributors are from the Transportation Sector, Energy Sector, Agriculture Sector and Solid Waste Sector. This has resulted in high carbon emissions in Kelurahan Menganti Keywords: Carbon emissions, CO2, Carbon Footprint, Settlements ABSTRAK Tingginya tingat kepadatan penduduk di Kecamatan Menganti menjadi potensi sebagai salah satu penyumbang emisi karbondioksida CO2. Emisi karbon yang dihasilkan yaitu dari sektor transportasi, energi, pertanian, peternakan dan persampahan. Rumusan Masalah dari penelitian ini adalah berapa nilai emisi karbon yang dihasilkan dari kegiatan permukiman di Kecamatan Menganti dan Bagaimana pemetaan jejak karbon yang dihasilkan dari kegiatan permukiman di Kecamatan Menganti. Tujuan dari penelitian ini untuk mengetahui nilai emisi karbon dan pemetaan nilai emisi karbon. Berdasarkan data yang diperoleh, nilai emisi dari Sektor Peternakan sebesar 461,78 ton CO2-eq/tahun, Sektor Persampahan sebesar 1537,01 ton CO2/tahun, Sektor Pertanian sebesar 2523,68 ton CO2-eq/tahun, Sektor Transportasi sebesar 2607,86 ton CO2-eq/tahun dan Sektor Energi sebesar 11203,96 ton CO2-eq/tahun. Hasil Pemetaan nilai emisi karbon tertinggi aktivitas permukiman di Kecamatan Menganti adalah Kelurahan Menganti dengan range 12275,03-16904,7 ton CO2-eq/tahun, penyumbang terbesar yaitu dari Sektor Transportasi, Sektor Energi, Sektor Pertanian dan Sektor Persampahan. Hal ini mengakibatkan tingginya Emisi Karbon di Kelurahan Menganti Kata Kunci: Emisi karbon, CO2, Jejak Karbon, Permukiman